Pepper necrotic spot virus, a new tospovirus infecting solanaceous crops in Peru - Torres, R (2012)
The authors wish to thank Dr. H. Pappu for his critical review of the manuscript and A. Redondo and I. de la Pena for technical assistance. This work was supported by Ministerio de Ciencia e Innovacion (grant RTA2009-00081), cofinanced by FEDER (European Fund for Regional Development). R. Torres was the recipient of funds from CONCYTEC (Consejo Nacional de Ciencia Tecnologia e Innovacion Tecnologica) during his stay in Madrid.